2010
DOI: 10.4162/nrp.2010.4.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of vegetables and related nutrients such as vitamin B complex, potassium, and calcium, are negatively correlated with risk of stroke in Korea

Abstract: Consumption of vegetables and fruits is associated with a reduced risk of stroke, but it is unclear whether their protective effects are due to antioxidant vitamins or folate and metabolically related B vitamins. The purpose of the study was to test the hypothesis that intake of fruits and vegetables, which are major sources of antioxidant and vitamin B complex vitamins, reduces the risk of stroke. Cases consisted of patients diagnosed with first event of stroke (n = 69). Controls (n = 69) were age-, sex-, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Recently, Park et al 19 . examined the relationship between fruit and vegetable intake and stroke in a South Korean hospital‐based case‐control study among 69 new‐onset stroke patients and 69 age‐, gender‐, and BMI‐matched controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Park et al 19 . examined the relationship between fruit and vegetable intake and stroke in a South Korean hospital‐based case‐control study among 69 new‐onset stroke patients and 69 age‐, gender‐, and BMI‐matched controls.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the FFQ used to measure dietary intake had not been validated, and the possibility of omission in capturing the entire intake of nutrients was noted. Other limitations included low participation in the study and low intake of fruits among the participants, with an average of one serving per day, thus failing to specify the link between fruit intake and risk of stroke 19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported a Canadian population to have low K (and high Na) intakes, and recommended increasing the consumption of dairy products, fruits and vegetables with the aim of reducing the high blood pressure values also recorded (40) . Certainly, Park (41) observed that participants who ate four to six servings of vegetables daily enjoyed a 32 % reduction in the risk of stroke, while those who consumed more than six servings daily enjoyed a reduction of 69 %, and that the intake of K (among other nutrients) showed a significant negative association with the risk of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A study at Hanyang University in Seoul, Korea, reported that the consumption of 4 to 6 servings of vegetables daily brought a 32% reduced risk of stroke. Six servings daily brought a 69% reduced risk of that disease, after adjusting for potential cofactors (11).…”
Section: Introductionmentioning
confidence: 99%